A nonsense mutation in mouse Tardbp affects TDP43 alternative splicing activity and causes limb-clasping and body tone defects. - Thomas Ricketts; Philip McGoldrick; Pietro Fratta; Hugo M de Oliveira; Rosie Kent; Vinaya Phatak; Sebastian Brandner; Gonzalo Blanco; Linda Greensmith; Abraham Acevedo-Arozena; Elizabeth M C Fisher (PLoS ONE, 2014)
Mutations in TARDBP, encoding Tar DNA binding protein-43 (TDP43), cause amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Attempts to model TDP43 dysfunction in mice have used knockouts or transgenic overexpressors, which have revealed the difficulties of manipulating TDP43, whose level is tightly controlled by auto-regulation. In a complementary approach, to create useful mouse models for the dissection of TDP43 function and pathology, we have identified a nonsense mutation in the endogenous mouse Tardbp gene through screening an N-ethyl-N-nitrosourea (ENU) mutant mouse archive. The mutation is predicted to cause a Q101X truncation in TDP43. We have characterised Tardbp(Q101X) mice to investigate this mutation in perturbing TDP43 biology at endogenous expression levels. We found the Tardbp(Q101X) mutation is homozygous embryonic lethal, highlighting the importance of TDP43 in early development. Heterozygotes (Tardbp(+/Q101X) ) have abnormal levels of mutant transcript, but we find no evidence of the truncated protein and mice have similar full-length TDP43 protein levels as wildtype littermates. Nevertheless, Tardbp(+/Q101X) mice have abnormal alternative splicing of downstream gene targets, and limb-clasp and body tone phenotypes. Thus the nonsense mutation in Tardbp causes a mild loss-of-function phenotype and behavioural assessment suggests underlying neurological abnormalities. Due to the role of TDP43 in ALS, we investigated potential interactions with another known causative gene, mutant superoxide dismutase 1 (SOD1). Tardbp(+/Q101X) mice were crossed with the SOD1(G93Adl) transgenic mouse model of ALS. Behavioural and physiological assessment did not reveal modifying effects on the progression of ALS-like symptoms in the double mutant progeny from this cross. In summary, the Tardbp(Q101X) mutant mice are a useful tool for the dissection of TDP43 protein regulation, effects on splicing, embryonic development and neuromuscular phenotypes. These mice are freely available to the community.